2020
DOI: 10.1063/5.0004550
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the Ti–Al system: Experimental study and molecular dynamics simulations

Abstract: The reactivity of the Ti-Al system was investigated experimentally in the case of reactive laminated particles produced by High Energy Ball Milling. The ignition temperature for self-sustaining reaction was measured as a function of the heating rate. By means of the Kissinger analysis, two activation energies were evaluated. The first one is associated to the solid state transformation at interface below the melting point of Al. The second one corresponds to the exothermic dissolution of Ti into Al liquid toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The influence of vacancies in this case is explained by the fact that diffusion under a solid-phase contact did not take place at all without any other defects with the given IPB orientation. This was also noted by the authors of [18], who explained it by high similarity of the atomic planes (0001) in Ti and (111) in Al (distances between the nearest atoms in these planes are very close for both metals: 2.951 and 2.864 Å at absolute zero respectively; this difference becomes even smaller under heating).…”
Section: Solid-phase Contact On the Ti−al Boundarysupporting
confidence: 72%
“…The influence of vacancies in this case is explained by the fact that diffusion under a solid-phase contact did not take place at all without any other defects with the given IPB orientation. This was also noted by the authors of [18], who explained it by high similarity of the atomic planes (0001) in Ti and (111) in Al (distances between the nearest atoms in these planes are very close for both metals: 2.951 and 2.864 Å at absolute zero respectively; this difference becomes even smaller under heating).…”
Section: Solid-phase Contact On the Ti−al Boundarysupporting
confidence: 72%
“…895.15 K is a typical temperature used in ref 9 Besides, multiple experimental studies show a temperature range of 825− 1220 K for Ti/Al system heat treatment. 14,9,10,31,32 2.2. Markov State Modeling Methods.…”
Section: Molecular Simulation Detailsmentioning
confidence: 99%
“…11−13 Moreover, a recent MD study combined with experiments on the reactivity of the Ti−Al system has identified an exothermic atom substitution process at the Ti/Al interface, where liquid Al atoms replace solid Ti atoms, leading to continued dissolution from areas where multiple Ti atoms have been substituted in close proximity. 14 Another recent study used MD to investigate the self-diffusion in liquid and solid alloys of the Ti−Al system. The results show that the activation energy of self-diffusion depends on the concentration of components and is smaller in disordered alloys than in ordered alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the structural transformation hcp → fcc of Ti atoms has been observed in Ti-Al multilayers as a function of bilayer thickness and orientation at interfaces [45,46]. Nanometric Ti-Al multilayers can nevertheless be very stable in specific conditions: the interface between (002)-Ti plane and (111)-Al plane is very stable because of the slight misfit between the two structures [47]. In this case, the solubility of Ti in Al is very limited in the solid state.…”
Section: Study Of Deformationmentioning
confidence: 99%